2003
DOI: 10.1523/jneurosci.23-04-01109.2003
|View full text |Cite
|
Sign up to set email alerts
|

Central Modulatory Neurons Control Fuel Selection in Flight Muscle of Migratory Locust

Abstract: Insect flight is one of the most intense and energy-demanding physiological activities. High carbohydrate oxidation rates are necessary for take-off, but, to spare the limited carbohydrate reserves, long-distance flyers, such as locusts, soon switch to lipid as the main fuel. We demonstrate that before a flight, locust muscles are metabolically poised for take-off by the release of octopamine from central modulatory dorsal unpaired median (DUM) neurons, which increases the levels of the potent glycolytic activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 23 publications
(42 reference statements)
0
56
0
Order By: Relevance
“…Previous studies suggested that OA acts as a potent, direct stimulator of flight muscle metabolism (Wegener, 1996;Mentel et al, 2003). Accordingly, we expected that especially prolonged flight would be affected in T␤H mutants, attributable to insufficient fuel supply.…”
Section: Sites Of Oa and Ta Actionmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous studies suggested that OA acts as a potent, direct stimulator of flight muscle metabolism (Wegener, 1996;Mentel et al, 2003). Accordingly, we expected that especially prolonged flight would be affected in T␤H mutants, attributable to insufficient fuel supply.…”
Section: Sites Of Oa and Ta Actionmentioning
confidence: 93%
“…OA and TA are decarboxylation products of the amino acid tyrosine, with TA as the biological precursor of OA. In insect flight systems, OA assumes a variety of physiological roles affecting central neuron excitability (Ramirez and Pearson, 1991), synaptic transmission (Evans and O'Shea, 1979;Leitch et al, 2003), sensory sensitivity (Matheson, 1997), hormone release (Orchard et al, 1993), and muscle metabolism (Mentel et al, 2003). Almost every organ is equipped with OA receptors (Roeder, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…2,4,5 Circulating levels of OCT are increased during "stressful" conditions, such as mobilization of lipids and sugars, so OCT is involved in adjusting an insect's body for a period of extended activity or assisting in recovery from a period of increased energy demand. [8][9][10][11][12][13][14][15] OCT produces a rapid increase in the circulating hemocyte population in response to bacterial challenge in some insects, such as the American cockroach, Periplaneta americana, and the beet armyworm, Spodoptera exigua. 16,17 It is suggested that OCT mediates cellular immune responses such as hemocytic phagocytosis and nodule formation via eicosanoids during bacterial invasion in insects.…”
Section: Introductionmentioning
confidence: 99%
“…In the jargon of the aeronautics industry, flight pushes the envelope of organism design (Dickinson, 1997). Flight muscle is one of the most widely studied flight-related tissues in insects mainly because of the variation in the metabolic activity of the different types of muscle (Sacktor, 1970;Usherwood, 1975, Mentel et al, 2003. All muscles receive excitatory innervation from glutamatergic neurons, inhibitory innervation from GABAergic neurons and modulatory innervation from octopaminergic dorsal unpaired median (DUM) neurons (Biserova & Pfluger, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The ultrastructure of the flight muscles, especially those associated with insect growth and development is well described (Herold, 1965;Reedy, 1968;Davies, 1974;Mizisin & Ready, 1986;Novicki, 1989;Reedy & Beall, 1993;Mentel et al, 2003;Biserova & Pfluger, 2004). The juvenile hormone (JH) is critical for both the growth and degeneration of flight muscles (Novicki, 1989;Rose, 2004).…”
Section: Introductionmentioning
confidence: 99%